EFEK ANTIINFLAMASI EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura L.) PADA MENCIT (Mus musculus) - Safriani Rahman; Aulia Wati; Eka Mega Asariningtyas (As-Syifaa Jurnal Farmasi, 2017)
Leaf cherry (Muntingia Calabura L) empirically been used by the public as an anti-inflammatory drug. Cherry leaf contains flavonoids are thought to have antioxidant effects. This study has been tested antiinflammatory effect of ethanol extract of leaves of cherry (Muntingia Calabura L) in mice (Mus musculus). A total of 15 mice were divided into 5 groups of 3 animals. Group I (control) are given Na.CMC 1% w/v, Group II, III, and IV (treatment) were given cherry leaf extract ethanol concentration of 1% w / v, 3% w / v, and 5% w / v, as well as groups V (comparison) given Diclofenac Sodium 0.195 mg / 30 gBW. Before treatment all groups karagen induced with 1% w / v in intraplantar. Antiinflammatory effect was measured using pleytismometer. The results were analyzed statistically by one-way ANOVA method. The results showed that the ethanol extract of cherry leaf has anti-inflammatory effects and the concentration of 3% and 5% w / v has an effect no different to that diclofenac sodium.